Problem-Based Learning Model and Discovery Learning Model by Learning Media: Students' Creative Thinking and Mathematical Collaboration Skills - Mardawati, Mardawati; Agustan, Agustan; Rukli, Rukli (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study intends to determine whether there is a difference in the creative thinking and mathematical collaboration abilities of students with the problem-based learning model and discovery learning model by learning media. The type of research used is quasi-experimental, a nonequivalent control group design. The research sample was 58 students from two elementary schools using the cluster random sampling technique. The data collection technique was carried out using a test and observation sheet, which were analyzed descriptively. The findings of the study indicated that (1) there is a difference in the creative thinking abilities of fourth-grade elementary school students between students taught the problem-based learning model and the discovery learning model. This finding is based on the results of the Paired-Sample T-Test analysis, which obtained a Sig value of 0.028 < 0.05. (2) There is a difference in the ability of fourth-grade elementary school students to collaborate in mathematics between students taught by the problem-based learning model and the discovery learning model. This is based on the results of the Paired-Sample T-Test analysis, which obtained a Sig value of 0.001 < 0.05. (3) For fourth-grade students, problem-based learning has a greater impact on their creative thinking and collaboration abilities compared to the discovery learning model. This is based on the results of the MANOVA analysis, which obtained a significant value of creative thinking ability showing 0.040 < 0.05 and a significant value of collaboration ability showing 0.001 < 0.05, so it can be concluded that H0 is rejected, and Ha is accepted.